Assessment of ADHD Symptoms and the Issue of Cultural Variation: Are Conners 3 Rating Scales Applicable to Children and Parents With Migration Background?. (May 2017) - Schmidt, Martin; Reh, Verena; Hirsch, Oliver; Rief, Winfried; Christiansen, Hanna
Objective : The objective was to evaluate whether Conners 3 ( Conners 3rd edition ) ratings of ADHD symptoms are robust to distortion by cultural variation when applied to children with migration background living in Germany.Method: From 2010 to 2011, Conners 3 data (self-rating, parent rating, and teacher rating) of 243 children with Turkish migration background, aged 6 to 16 years, were collected in various German schools. Allocation of items to latent factors was tested with confirmatory analyses. Reliability and validity of resulting factors was calculated and influence of acculturation, gender, and age on rating-modalities was examined.Results: Confirmatory factor analyses showed high model fits for all rating-modalities. Resulting scales had good reliability and validity. There was a small influence of acculturation on parent ratings of oppositional defiant disorder but not on ADHD core symptoms.Conclusion: Conners 3 ratings seem to be robust against influences of cultural variation. Their German translation can be utilized for children with Turkish migration background without limitation.